2015
DOI: 10.1007/s11095-015-1791-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Properties of a Novel d-Peptide Developed to be Therapeutically Active Against Toxic β-Amyloid Oligomers

Abstract: These excellent pharmacokinetic properties confirm that RD2 is a very promising drug candidate for AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 34 publications
0
40
0
1
Order By: Relevance
“…protease‐resistant), non‐toxic and can readily penetrate the blood–brain barrier in wildtype mice via different routes of administration (Leithold et al . ; Jiang et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…protease‐resistant), non‐toxic and can readily penetrate the blood–brain barrier in wildtype mice via different routes of administration (Leithold et al . ; Jiang et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…We next sought to investigate whether known inhibitors of human pathological amyloid formation would effectively inhibit CsgA fibrillation on the basis of this proposed structural similarity. We tested a group of synthetic D-enantiomeric peptides (referred to here as D-peptides) designed against Aβ (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65). Two of the D-peptides tested, ANK6 and DB3DB3 (60), were found to inhibit CsgA fibrillation in dose-dependent manners.…”
Section: Csga Shares Fibrillation Inhibitors With Aβmentioning
confidence: 99%
“…The structural similarity between fibrillar spine segments derived from CsgA and those derived from human pathological amyloids prompted us to investigate whether fibrillation inhibitors designed against human amyloids could also inhibit curli formation. Accordingly, we found that two D-enantiomeric peptides, originally designed to interfere with the formation of oligomers of Alzheimer's disease-associated Aβ (55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65), inhibited the fibrillation of CsgA spines as well as of full-length CsgA and reduced biofilm formation in curli-expressing Salmonella typhimurium in dosedependent manners. These results provide structural insights into a biofilm-related amyloid and pave the way for the rational development of anti-microbial drugs targeting amyloid-structured biofilms.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, we have identified a number of D-enantiomeric peptides as promising drug candidates for direct elimination of A␤ oligo (25)(26)(27)(28)(29)(30). The advantage of D-peptides over L-peptides is their higher protease resistance, resulting in slower degradation and longer half-life (31,32).…”
mentioning
confidence: 99%
“…Treatment with D3 reduces the number of amyloid plaques (26) and improves cognition in transgenic AD mice (28). One derivative of D3 called RD2 shows enhanced binding to A␤ (36, 37), and both RD2 and D3 have demonstrated desirable pharmacokinetic properties (29,38). A further promising derivative is the D-peptide RD2D3, a head-to-tail tandem combination of RD2 and D3 (30,34,39).…”
mentioning
confidence: 99%